O paradoxo da proteção e da cidadania de adolescentes transexuais e travestis - Vinício Araújo Martins (2024)
This study investigates and discusses the paradox of protection and citizenship of transgender and transvestite adolescents, focusing on adolescents in situations of restriction or deprivation of liberty. The presented material is based on documental analysis, theoretical references on adolescence, gender diversity, socio-education, and the rights of children and adolescence, as well as material obtained through conversations with transgender adolescents deprived of liberty and professionals who work in the socio-educational system. It also includes data from a public hearing held in Belo Horizonte to address episodes of transphobia within socio-educational units and propose ways to confront and eliminate this phenomenon. The premise of the research was the invitation extended to the Janela da Escuta Extension Program (UFMG) to contribute to a plan to combat transphobia in the socio-educational system. The objectives are to discuss how transphobic violence manifests itself in relation to adolescents serving socio-educational measures of deprivation or restriction of liberty, as well as to understand how transphobia is a structuring element of the lack of protection for these individuals. The collected material and the discussion carried out point to a scenario where prejudice and rejection of these individuals mark a situation of lack of protection, vulnerability, and difficulties in accessing public policies and protection. The dissertation is organized into two major articles. The first article, organized into five sections, focuses on the discussion of the notion of adolescence for psychoanalysis, aspects of the singularity of transitions, and an overview of segregation and lack of protection for this group in Brazil. The second article, organized into seven sections, focuses more on elements of socio-educational policy, the experiences of transgender adolescents serving socio-educational measures, and the experience of transphobic situations as manifestations of rejection of these people.